Crystal engineering of nanomaterials: current insights and prospects. Issue 45 (8th July 2021) - Görke, Marion; Garnweitner, Georg
Abstract : Nanocrystal engineering has evolved into a dynamic research area over the past few decades but is not properly defined. Here, we present select examples to highlight the diverse aspects of crystal engineering applied on inorganic nanomaterials. Abstract : The rather loosely defined field of crystal engineering offers a wide variety of approaches towards the precise design of nanocrystals for different applications. Thereby, inorganic nanomaterials have been in the focus of research due to their highly interesting characteristics, and the possibility to obtain fascinating structures and morphologies at the smallest size scales. Despite great progress and a steady increase in complexity of the synthesized materials, the targeted preparation of nanocrystals however is still only feasible to a limited extent. Further intensification of the cross-disciplinary exchange of results and insights in nanocrystal engineering on a joint platform like CrystEngComm can accelerate the development of unifying concepts in crystal design and an understanding of structure–property relations. Therefore, this article aims to present the diversity of nanocrystal engineering research, by highlighting some of the most intriguing research results over the past few years.